The Export Performance of Sub-Saharan Africa, 1970-19+L69390 : A Survey - Greene, Joshua (IMF Working Papers; Working Paper, 1992)
The export performance of Sub-Saharan Africa has lagged behind that of developing countries in other regions for the past two decades, and total export proceeds have fallen significantly since 1980. Many factors explain this outcome, including continued concentration in slowly-growing non-fuel primary commodities and domestic economic policies that have discouraged new investment that could promote diversification and increased production of traditional crops. Diversification into new agricultural products and light manufactures could boost export earnings, but only if the region can compete successfully with existing producers elsewhere. In most countries this will require major structural reforms to create a more attractive economic environment.